Frontispiece: Pedal to the Metal: The Homogeneous Catalysis of the Native Chemical Ligation Reaction. Issue 16 (16th March 2022) - Diemer, Vincent; Firstova, Olga; Agouridas, Vangelis; Melnyk, Oleg
Abstract : Homogeneous nucleophilic catalysis is key to the acceleration of the native chemical ligation (NCL) reaction and thus to its application to protein semi or total synthesis and utilization in chemical biology. The concept article by V. Diemer et al. discusses the fundamental principles of NCL rate and catalysis and is presented as a guide for readers in the search for an appropriate catalyst.